The performance of green carbon as a backbone for hydrogen storage materials. (27th March 2020) - Jang, Hyun-Seok; Mun, Junyoung; Hong, Won G.; Lee, Sang Moon; Jeon, Jun Woo; Lee, Chang Yeon; Kim, Hae Jin; Kim, Byung Hoon
Abstract: We investigate the use of carbonized bamboo, which has an organic porous structure, as a hydrogen storage material. Bamboo samples were thermally treated at 800, 900, 1000, and 1100 °C for 24 h. The pore size and hydrogen storage capacity of each sample were measured by N2 and H2 gas sorption up to 1.13 bar at 77 K. The maximum hydrogen storage was exhibited by the sample treated at 900 °C, which reached 1.35 wt% at 1.13 bar/77 K. The results showed that the bamboo, one of the green carbons, has the potential to be used as an environmental-friendly carbon backbone for hybrid hydrogen storage materials. Highlights: Phyllostachys bambusoides (PB)-based porous green carbon was synthesized by thermal treatment from 800 to 1100 °C. Maximum hydrogen storage capacity of PB reached up to 1.35 wt% at 1.13 bar/77 K. PB is a low-cost, high performance, and eco-friendly material compared with chemically synthesized carbon materials. Natural derivative, PB, can be adapted to a backbone for the metal hydride/carbon hybrid for hydrogen storage.